The Islamic Religion in Course Curriculums of High School History Textbooks in The Republic of North Macedonia - Zećir Ramčilović; M. Sayyidul Abrori (Journal of Contemporary Islamic Education, 2023)
History textbooks besides educating students can also deepen the divisions, prejudices and uncritical attitudes contrary to the goals of education, and the youth population is the most vulnerable group. To that end, the main goal of this paper is to analyze the teaching contents of high school textbooks related to religion. In particular, this paper examines the role of religion in the formation of Balkan nations, which have made it one of the key elements of their national identities. Due to the large volume of content related to the religion, as well as the mere fact that Muslims are the second largest religious group in North Macedonia, this paper analyzes the contents which are related only to the Islamic religion. The literature review and the overview of the legal framework will give an additional impulse to the efforts of eliminating those parts of the teaching contents that create division and prejudices, and thus, its studying can become the key factor in the building of trust between people of different religions.